Tempo and Mode of Diversification of Lake Tanganyika Cichlid Fishes - Day, Julia J. (Public Library of Science, 2008)
BACKGROUND: Understanding the causes of disparities in species diversity across taxonomic groups and regions is a fundamental aim in evolutionary biology. Addressing these questions is difficult because of the need for densely sampled phylogenies and suitable empirical systems. METHODOLOGY/PRINCIPAL FINDINGS: Here we investigate the cichlid fish radiation of Lake Tanganyika and show that per lineage diversification rates have been more than six times slower than in the species flocks of Lakes Victoria and Malawi. The result holds even at peak periods of diversification in Lake Tanganyika, ruling out the age of the lake as an explanation for slow average rates, and is robust to uncertainties over the calibration of cichlid radiations in geological time. Moreover, Lake Tanganyika lineages, irrespective of different biological characteristics (e.g. sexually dichromatic versus sexually monochromatic clades), have diversified at similar rates, falling within typical estimates across a range of plant and animal clades. For example, the mostly sexually dichromatic haplochromines, which have speciated explosively in Lakes Victoria and Malawi, have displayed modest rates in Lake Tanganyika (where they are called Tropheini). CONCLUSION/SIGNIFICANCE: Our results show that either the Lake Tanganyika environment is less conducive for cichlid speciation or the remarkable diversifying abilities of the haplochromines were inhibited by the prior occupancy of older radiations. Although the results indicate a dominant role for the environment in shaping cichlid diversification, differences in the timing of diversification among the Tanganyikan tribes indicate that biological differences were still important for the dynamics of species build-up in the lake. While we cannot resolve the timing of the radiation relative to the origin of the lake, because of the lack of robust geological date calibrations for cichlids, our results are consistent with a scenario that the different clades reflect independent adaptive radiations into different broad niches in the lake.